Evaluation of the implementation of a best practice gestational diabetes model of care in two Australian metropolitan services. Issue 1 (8th March 2022) - Wilkinson, Shelley A.; Palmer, Michelle; Smith, Shelley; Porteous, Helen; McCray, Sally
ABSTRACT: Introduction and aims: Dissemination and local adaptation of best practice models of care are often poorly achieved in knowledge translation processes. Understanding and documenting the iterative cycles of improvement can elucidate barriers, enablers and benefits of the process for future adoption and service integration improvements. This project examined the process of local adaptation for a third stage translation of a gestational diabetes dietetic model of care through collaboration with two Queensland (Australia) hospitals. Methods: Using a hub (research team)-spoke (sites) model, two Queensland Hospital and Health Service Districts were supported to assess and address evidence-practice dietetic model of care gaps in their gestational diabetes mellitus (GDM) services. Sites selected demonstrated strong GDM team cohesiveness and project commitment. The project phases were: Consultation; Baseline; Transition; Implementation; and Evaluation. Results: Despite strong site buy-in and use of a previously successful model of care dissemination and adoption strategy, unexpected global, organisational, team and individual barriers prevented successful implementation of the model of care at both sites. Barriers included challenges with ethics and governance requirements for health service research, capacity to influence and engage multidisciplinary teams, staff turnover and coronavirus disease 2019's (COVID-19's) disruption to service delivery. Conclusion: This third iteration of the dissemination of a best practice model of nutrition care for GDM in two Queensland Hospital and Health Service Districts did not achieve successful clinical or process outcomes. However, valuable learnings and recommendations regarding future clinical and research health service redesign aligned with best practice are suggested.